Antioxidant activity (2-2-diphenil-1-picrilhydrazil radical-scavenging assay) and phytochemicals of Mimosa invisa Colla and Mimosa pigra L. grown at different terrestrial habitats. - Chaniago, Irawati; Setiawan, Ryan Budi; Ardi, Ardi; Hariandi, Doni; Sari, Winda Purnama (Universitas Padjadjaran, 2025)
Giant false sensitive plants (Mimosa invisa Colla) and giant sensitive plants (Mimosa pigra L.) are invasive plant species in the tropics and native to America. They are widely distributed in different ecosystems and soil types. Apart from being considered woody shrub weeds, these plant species can be used as herbal medicine for their antioxidant activities. An experiment to study the antioxidant activities and phytochemicals of M. invisa and M. pigra grown at 200 m from the coastline and close to the riverbank (riparian abandoned land) was carried out from March to November 2023. Weed leaves were collected as purposive randomized sampling from different terrestrial habitats in the City of Padang, West Sumatra. Antioxidant activity was identified according to a 2-2-diphenyl-1-picrilhydrazil (DPPH) radical-scavenging assay, and phytochemical compounds were identified qualitatively. Results demonstrate that M. invisa had mild antioxidant activity and M. pigra had strong antioxidant activity. The IC50 values for M. invisa grown at 200 m from the coastline and at the riverbank were 121.3 ± 11.5 and 105.6 ± 2.90 ppm, respectively. The IC50 values of M. pigra grown at 200 m from the coastline and at the riverbank were 80.6 ± 15.9 and 85.1 ± 9.03 ppm, respectively. Phenolic, saponin, and steroid were detected in all weeds grown at different habitats. However, alkaloids and terpenoids were not detected. Interestingly, flavonoid was not detected in the leaves of M. pigra grown at the riverbank.